STRESS MANAGEMENT ON EMPLOYEE PERFORMANCE - MUSIIMENTA DORCUS (My University, 2024)
This concept of stress management is recognized as a best practice for Human resource management and has been found with vital and crucial effect on the employee performance because it leads to either productivity or unproductivity of employees. Therefore, this research explores the relationship between stress management practices and employee performance within the 7 star cleaning services at Uganda Christian University. The performance of employees leads to the achievement of organizational goals and objectives though it can be affected by work related stress which in the end reduces productivity, increases absenteeism and reduces job satisfaction. This study therefore aims to identify how effective stress management can enhance employee performance in an environment with stress. In this study a mixed methods approach was used, both quantitative from the structured questionnaires and qualitative from the interviews with the 92 employees. The study revealed a positive correlation between stress management practices and employee’s performance which indicated that positive stress management leads to improved productivity. Stress management practices that were identified include supportive leadership, effective communication and resources to mitigate resources should be provided. The findings show that 7star is a high stress sector since it provides cleaning services so stress management practices have to be implemented. Therefore, through implementing a supportive environment, there would be an improvement in employee well-being enhance performance and reduce costs associated with poor performance. In conclusion, there is need for continuous training on stress management practices and culture of supportive leadership employed.